1996
DOI: 10.1007/bf00862081
|View full text |Cite
|
Sign up to set email alerts
|

Superior sagittal sinus thrombosis in a child with nephrotic syndrome

Abstract: A 3-year-old male with steroid-responsive nephrotic syndrome developed a rare complication, sagittal sinus thrombosis during an episode of gastroenteritis, while on steroid therapy. Anticoagulation, as assessed by partial thromboplastin time, was difficult to maintain, despite administering high doses of heparin, infusions of fresh-frozen plasma to provide antithrombin III, and, subsequently, maximum doses of warfarin (0.3 mg/kg per day). Despite these problems the child made a complete neurological recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…However, the prevalence of thromboembolism in NS is thought to be underestimated [23,52]. Divekar et al have observed a single case of CSVT among 700 hundred consecutive patients with NS [12].…”
Section: Discussionmentioning
confidence: 98%
“…However, the prevalence of thromboembolism in NS is thought to be underestimated [23,52]. Divekar et al have observed a single case of CSVT among 700 hundred consecutive patients with NS [12].…”
Section: Discussionmentioning
confidence: 98%
“…Divekar et al reported only 1 case of CST out of 700 children with nephrotic syndrome followed over a period of 17 years 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis of various vessels has been reported, but CST associated with nephrotic syndrome appears to be very rare and only a few isolated reports exist in the literature [2][3][4][5][6][7][8][9][10][11][12][13] . Divekar et al reported only 1 case of CST out of 700 children with nephrotic syndrome followed over a period of 17 years 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations